The influence of gibberellic acid on the chlorophyll fluorescence, protein content and PAL activity of wax apple (Syzygium samarangense var. jambu madu) fruits - Mohammad Moneruzzaman, Khandaker; Amru Nasrulhaq, Boyce; Ali, Majrashi (Southern Cross Publishing and Printing Pty Ltd, 2015)
A study was carried out to investigate the effects of gibberellic acid on chlorophyll fluorescence, phenylalanine ammonia lyase (PAL) activity and anthocyanin biosynthesis in Syzygium samarangense var. jambu madu fruits. Selected horticultural parameters were monitored during the growth period from May 2014 to April 2015 using different concentrations of GA3 ranging from 20 to 100 mg L⁻¹. Results revealed that 50 mg L⁻¹ GA3 treatment increased chlorophyll content, soluble protein and produced the highest chlorophyll fluorescence and quantum yield. It was observed that 50 mg L⁻¹ GA3 treatments increased the PAL activity and anthocyanin content of fruits significantly. Furthermore, a positive correlation (R2 = 0.69) between the PAL activity and anthocyanin biosynthesis was observed in treated fruit. With regard to fruit maturity, red ripen stage showed the highest PAL activity and anthocyanin content. From this study, it can be concluded that 50 mg L⁻¹ GA3 once each week from the beginning of flower opening through fruit development, exhibited highest chlorophyll fluorescence and quantum yield, stimulated PAL activity and anthocyanin biosynthesis of the jambu air madu fruits under field conditions.